A coupled wear and crack initiation-propagation methodology for fretting fatigue life assessment in press-fitted axles. (June 2022) - Zou, Lang; Zeng, Dongfang; Zhang, Yuanbin; Lu, Liantao; Zhao, Hai; Xu, Tian; Shi, Guanghan; Chen, Han
Highlights: A methodology coupled with the fretting wear, crack initiation, and propagation is proposed for fatigue life assessment of press-fitted axles. The theory of critical distance is used to define the critical crack length between the crack initiation and propagation stages. A method for acquiring the optimized energy wear coefficient is proposed from a simulation viewpoint. The proposed methodology presents a good prediction for the fretting fatigue life of press-fitted axles. Abstract: A methodology that coupled the fretting wear, crack initiation, and propagation was firstly proposed for the total fatigue life assessment of press-fitted axles. The Smith–Watson–Topper (SWT) fatigue indicator parameter (FIP), the theory of critical distance (TCD), and the Miner damage rule were adopted to estimate the crack initiation. The contour integral method and the Paris's law were used to predict the crack propagation. Furthermore, fretting wear was simulated using the energy wear approach. The simulation results showed that TCD used in this methodology could mitigate high-stress gradient effects, and define the critical crack length for crack initiation and propagation prediction. The crack initiation prediction provided accurate information about the initial crack angle and site for the propagation estimation. The Maximum Tangential Stress criterion considering the wear effect could reasonably predict the crack propagation path of press-fitted axles. As compared with the total fatigue life predicted by the SWT FIP alone, the proposed methodology provided a better prediction result.